Effect of some factors on the growth and regeneration of cell suspension of Ngoc Linh ginseng (Panax vietnamensis Ha et Grushv.) - Cương, Lê Kim; Hoàng, Nguyễn Hồng; Nhựt, Dương Tấn (Vietnam Journal of Biotechnology, 2016)
Ngoc Linh ginseng also known as Vietnamese ginseng (Panax Vietnamensis Ha et Grushv.) is a perennial medicinal plant. This plant is extremely rare and belongs to the Araliaceae family. Scientists are focusing on studies of Ngoc Linh ginseng nowadays. In this research, the effects of 2,4-dichlorophenoxyacetic acid (2,4-D), a-naphthaleneacetic acid (NAA), indole-3-butyric acid (IBA), 6-benzylaminopurine (BA), Kinetin (KIN), mineral salt formulations and cultural conditions, pH, sucrose concentration, medium volume on cell suspension culture of Panax vietnamensis Ha et Grushv. were investigated. In addition, growth curves and the effect of several plant grow regulators including a-naphthaleneacetic acid (NAA), indole-3-butyric acid (IBA), 6-benzylaminopurine (BA) on the regeneration of Ngoc Linh ginseng‘s cell suspension were also presented in this study. After 28 days in culture, the results showed that the best growth of a cell suspension of Ngoc Linh ginseng were obtained on ½MS liquid medium supplemented with 1.5 mg/l NAA, 50 g/l sucrose and the most suitable pH was 6.3. The acceptable medium volume for cell suspension growth was 30 ml. The growth curve of Ngoc Linh ginseng’s cell suspension showed that it should be subcultured at the beginning of the stationary phase approximately the 14th-16th day of culture. Ngoc Linh ginseng’s cell suspension exhibited the strongest growth at this time. When Ngoc Linh ginseng’s cell suspension was transferred to fresh medium, somatic embryos were formed in MS medium supplemented with 3.0 mg/l NAA after 30 days culture. The results shown that the potential regeneration of cell suspension of Ngoc Linh ginseng is very high